2004
DOI: 10.4049/jimmunol.172.9.5727
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase and Akt Occupy Central Roles in Inflammatory Responses of Toll-Like Receptor 2-Stimulated Neutrophils

Abstract: Neutrophils are critical initiators and effectors of the innate immune system and express Toll-like receptor 2 (TLR2) and TLR4. Although signaling through pathways involving phosphoinositide 3-kinase (PI3-K) and the downstream kinase Akt (protein kinase B) plays a central role in modulating neutrophil chemotaxis and superoxide generation in response to engagement of G protein-coupled receptors, the importance of these kinases in affecting inflammatory responses of neutrophils stimulated through TLR2 has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 58 publications
12
105
2
Order By: Relevance
“…Indeed, it was recently reported that Akt modulates NF-B-dependent transcription in TLR2-stimulated PMN by modifying phosphorylation of the p65 subunit (7). Nevertheless, Akt is necessary but not sufficient for NF-B activation by TLR (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was recently reported that Akt modulates NF-B-dependent transcription in TLR2-stimulated PMN by modifying phosphorylation of the p65 subunit (7). Nevertheless, Akt is necessary but not sufficient for NF-B activation by TLR (51).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these shared pathways, TLRs probably show differences in their rate, intensity, or efficiency of activation, involving unidentified mechanisms. Selective pathways are reported to be triggered by some TLRs; in particular, TLR2, TLR4, and TLR9 can activate the PI3K pathway (6,7). Activation of cell signaling cascades triggers immune responses leading to pathogen eradication.…”
mentioning
confidence: 99%
“…However, how these receptors are linked to TNF production is not yet fully understood. Although some evidence shows that engagement of TLR2 or TLR4 can activate the PI3K/Akt pathway and increase TNF production [15,16], other work has indicated that PI3K/Akt activation negatively regulates TLR signaling in macrophages while positively regulating FccR signaling required for phagocytosis. Inhibition of PI3K in macrophages enhances LPS-induced activation of Erk, Jnk, p38 and NF-jB, increases LPS-induced induction of TNF and IL-6, stimulates inducible nitric oxide synthase (iNOS) expression and nitric oxide (NO) synthesis, and reduces the survival of endotoxemic mice [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…PI3K was shown to regulate MyD88-dependent events [23][24][25][26] but its role in the TRIF-dependent signaling cascade has not been demonstrated so far. To investigate this question, we first determined the effects of pharmacological inhibition of PI3K activity on IFN-b synthesis and activation of NF-jB and IRF3 transcription factors in human monocytederived DC stimulated by poly(I:C) or LPS used as TLR3 and TLR4 ligands, respectively.…”
Section: Introductionmentioning
confidence: 99%